2013
DOI: 10.1289/ehp.1206335
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Environmental Phenols: Concentrations in Amniotic Fluid and Variability in Urinary Concentrations during Pregnancy

Abstract: Background: Maternal urinary biomarkers are often used to assess fetal exposure to phenols and their precursors. Their effectiveness as a measure of exposure in epidemiological studies depends on their variability during pregnancy and their ability to accurately predict fetal exposure.Objectives: We assessed the relationship between urinary and amniotic fluid concentrations of nine environmental phenols, and the reproducibility of urinary concentrations, among pregnant women.Methods: Seventy-one women referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
156
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(179 citation statements)
references
References 41 publications
(33 reference statements)
19
156
3
1
Order By: Relevance
“…For example, as noted by Koch et al (2014), "In many cases the relatively high ICC values in the current study derived from large between-individual differences in exposure levels rather than from low within-individual variation … " Koch et al further observe that a single spot sample may "substantially over-or under-represent average exposure to that individual." Similarly, referring to ICCs of around 0.5-0.6, Philippat et al (2013) stated: "Although a correlation of this magnitude is greater than reported for many other rapidly metabolized compounds, it may still result in bias due to exposure misclassification if the putative window of susceptibility is distant from the sample collection period … To limit the effects of exposure misclassification, studies of the effects of phenol prenatal exposure on health should try to collect multiple urine samples during pregnancy. "…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…For example, as noted by Koch et al (2014), "In many cases the relatively high ICC values in the current study derived from large between-individual differences in exposure levels rather than from low within-individual variation … " Koch et al further observe that a single spot sample may "substantially over-or under-represent average exposure to that individual." Similarly, referring to ICCs of around 0.5-0.6, Philippat et al (2013) stated: "Although a correlation of this magnitude is greater than reported for many other rapidly metabolized compounds, it may still result in bias due to exposure misclassification if the putative window of susceptibility is distant from the sample collection period … To limit the effects of exposure misclassification, studies of the effects of phenol prenatal exposure on health should try to collect multiple urine samples during pregnancy. "…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Data from this study showed that t,t-MA, HA, and MHA have a good correlation with concentrations of the related hydrocarbons. Many studies have confirmed these results (33)(34)(35), but some studies reported a poor correlation between t,t-MA and benzene (36). Angerer et al reported a poor correlation between HA and toluene (37).…”
Section: Discussionmentioning
confidence: 84%
“…This is an area which requires future scientific investigations. The decreasing concentrations of BP-3seen in urine during pregnancy probably reflect transfer of BP-3 to the developing fetus since BP-3 has previously been detected in amniotic fluid [5]. The observed decreases in concentrations of BP-3 during pregnancy could potentially be due to modification of drug half-life.…”
Section: Discussionmentioning
confidence: 87%
“…BP-3 has also been detected in both raw and water treated by water filtration plants [2] in California, in waste water in Slovenia and in Switzerland [3,4]. BP-3 has been detected in urine of pregnant females and more than half of the amniotic fluid samples [5] with a high correlation of 0.53 between their concentrations in maternal urine and amniotic fluid. In a study of 105 pregnant females in Northern Puerto Rico [6], BP-3 was detected in 100% the urine samples and the levels of BP-3 among Puerto Rican pregnant females were found to be higher than females of reproductive age in general US population (52.2 ng/mL vs. 38.6 ng/mL for NHANES 2007-2008 and 36.3 ng/mL for NHANES [2009][2010].…”
Section: Introductionmentioning
confidence: 99%